Healthy Eating for Elders: Super Sandwiches - Jennifer Hillan (EDIS)
Sandwiches can make a quick, easy, and nutritious meal when combined with a side of fruit and a glass of milk. This document contains tips to create some new sandwich favorites!  This is document FCS 8699-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: February 2005.